The Impact of Celebrity Endorsements on Consumer Purchase Behaviour: An Indian Perspective - Udhwani, Hiten (2011)
Celebrities in India have been endorsing products since a very long time. Indian consumers have been exposed to celebrities representing products and being the face behind a brand, which as a strategy is being used by almost all multi-national companies to attract consumers and create an appeal for their brand/product. Celebrity endorsement as a marketing technique has become very vital for communicating to the public as the celebrity is able to stand out from the clutter of communication. A country like India is very well known for their diverse cultures, spices, cinema and cricket. The Indians idolize and worship their Bollywood actors/actresses and cricketers. Indians aspire to be like these personalities and imitate their behavior and choices. Marketers and advertisers see this as an opportunity to capitalize by influencing consumers’ purchase behavior through celebrity endorsements. This dissertation focuses on understanding and exploring the opinions and perceptions of Indian consumers about the celebrity endorsements as a process and its impact on their purchase behavior. The research project commences with a brief introduction about celebrity endorsements and its history. The next chapter is literature review, which includes theories, models and how it came to be one of the most common methods of promoting products/brands; this is followed by the research objective and aim. The next chapter describes details about the method used to collect data and sampling strategy. In depth qualitative interviews were conducted as an approach to investigate the mind-set of Indian consumers towards celebrity endorsements and does it affects their choices. Interesting responses under findings were derived from the in depth interviews, which were then analyzed and discussed based on the theories and models illustrated and explained in the literature review. The final chapter includes the conclusion, limitations to research, managerial implications and scope for future research.